The Presumption of Atheism according Zubiri - Solari, Enzo (Pensamiento. Revista de Investigación e Información Filosófica, 2020)
This paper shows how the whole of Zubiri’s work —incorporating his recently edited texts and courses— argued against a favorable presumption of atheism, and instead suggested that atheism remains in identic intellectual status that theism and agnosticism. In order to do this, the paper rebuilds in Zubiri’s mature philosophy, his analyses about an atheistic logos and a reason of atheism, and at the end it adds some practical and political perspectives in order to explain this philosophy of atheism.
Keywords: atheism; philosophy of religión; phenomenology; logos; reason